Someone like you - Kelly, Cathy (Dublin, Ireland : HarperCollins, London, 2000)
Emma, Leonie and Hannah all want just one thing in life - and then they'll be truly happy. But sometimes when you wish with all your heart for a dream to come true, you risk destroying the happiness within your reach
Keywords: Female friendship -- Fiction; Women -- Ireland -- Fiction; Irish -- Egypt -- Fiction; Ireland -- Fiction; Egypt -- Fiction